PROFIL KASUS BUNUH DIRI DI KOTA MANADO PERIODE JANUARI-NOVEMBER 2015 - Mantiri, Arthur D. B.; Kristanto, Erwin; Siwu, J. (e-CliniC, 2016)
Abstract: Suicide has been seen as one final solution. For some people, suicide has become the one and only way towards a solution of the pressing problems of life. Life ending is an alternation to be free of life troubles. Nowadays, suicide has become a global problem. Each year there are more than 800,000 people who committed suicide and many others who tried to commit suicide. The results showed that the incidence of suicide in Manado was lower thhan the the other regions in Indonesia such as Bali and Mount Kidul. However, comparing to its surrounding areas Manado has a higher incidence. From all suicide cases in Manado, 100% chose hanging oneself as the most preferred method. Most cases were males aged 11-20 years and 31-40 years.Keywords: commit suicide, hangingÂ Abstrak: Bunuh diri telah dipandang sebagai salah satu penyelesaian masalah. Bagi sebagian orang, bunuh diri telah menjadi satu - satunya jalan menuju solusi dari masalah hidup yang menekan. Mengakhiri hidup menjadi alternatif untuk bebas dari masalah hidup. Bunuh diri telah menjadi suatu masalah global. Tiap tahun lebih dari 800.000 orang yang melakukan tindakan bunuh diri dan masih banyak lagi yang mencoba untuk bunuh diri. Hasil penelitian memperlihatkan bahwa angka kejadian bunuh diri di Manado lebih rendah dibandingkan dengan daerah lain di Indonesia seperti Bali dan Gunung Kidul. Namun dibandingkan dengan daerah sekitarnya, Manado memiliki angka kejadian yang lebih tinggi. Dari semua kasus bunuh diri di Manado, 100% melakukan gantung diri. Pelaku bunuh diri terbanyak ialah laki-laki berusia 11-20 tahun dan 31-40 tahun. Kata kunci: bunuh diri, gantung diri